The impact of nutrition awareness on society (Eurasian Journal of Research, Development and Innovation, 2024)
The enzymes included in the oxidative protection system of the technological cycle of processing white and red grape varieties have been studied. It has been established that some technological operations predetermine an increase in oxidative stress. When processing red grapes, bound forms of SO2 increase, which reduces its antioxidant properties. Sulfation of red wort in the amount specified in the technological instructions is clearly not enough to provide antioxidant protection